1993
DOI: 10.2169/internalmedicine.32.430
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Post-Anoxic Encephalopathy without Relation to Carbon Monoxide Poisoning.

Abstract: Delayed post-anoxic encephalopathy (DPE) not related to carbon monoxide has rarely been reported and usually carries a poor prognosis. Wedescribe two surviving patients with such DPE and its neuro-otological characteristics. The DPEwas caused by shock due to hemorrhage in a 21-year-old student, and by severe hypoxia and hypotension in a 60-year-old man. Our findings suggest that this type of DPEmight not be rare, if the patients whosuffered from severe anoxia, marked hypotension or both are carefully observed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Levodopa and rehabilitation therapy was started. Hyperbaric oxygen therapy was also undertaken for 21 days [2]. Her family decided to deny surgery until functional recovery.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Levodopa and rehabilitation therapy was started. Hyperbaric oxygen therapy was also undertaken for 21 days [2]. Her family decided to deny surgery until functional recovery.…”
Section: Case Reportmentioning
confidence: 99%
“…Delayed neurologic deterioration after an initial recovery following hypoxic-ischemic injury has rarely been reported, and has most commonly been associated with carbon monoxide (CO) poisoning. It has also been occasionally reported after respiratory depression, cyanosis, shock, strangulation, cardiac arrest, complications of surgery and anesthesia and drug overdose with heroin or benzodiazepine [2][3][4][5]. We present a patient with early GP necrosis followed by delayed substantia nigra (SN) damage and leukoencephalopathy on serial magnetic resonance imaging (MRI) after hypoxic-ischemic injury.…”
Section: Introductionmentioning
confidence: 99%
“…Lou et al reported a case of delayed hypoxic encephalopathy following gastrointestinal hemorrhage in which the patient displayed symmetrical involvement of the bilateral globus pallidus and the substantia nigra (9). Mizutani et al also described a case of delayed hypoxic encephalopathy following shock associated with a contusion and laceration of the liver in a traffic accident (10). The previously reported patients were resuscitated before developing hypoxic encephalopathy (9, 10); therefore, hypoxic-hypoxia rather than anemic hypoxia may have been the primary mechanism for their ischemic brain injuries.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although the main cause of DAE is CO intoxication, DAE also results from other medical conditions, such as shock and hypoxia. 3,4 To date, there have been three case reports on elevated mood as a symptom of DAE following various medical conditions. 5-7 Yagnik et al 5 reported two patients, who had a history of drug intoxication and depression, who developed DAE after attempting suicide.…”
Section: Introductionmentioning
confidence: 99%